SIMULASI PENGELOLAAN SAMPAH KOTA DENGAN POWERSIM - Setia Budi Sasongko (TEKNIK, 2008)
This article is developed based on the previous articles in this journal about municipa solid waste (MSW)or rubbish in municipal which should be well managed to withdraw from negative effect. Based on thesecondary data can be prepared computation model using Powersim as the objective of this article.Application of Powersim is also discussed in this article to develop operation of the simulator. Thesimulation of the municipal solid waste management is the action to replicate the real situation or event toget the effect or appearance system. The results of computation model by Powersim can be simulatedseveral activities of the municipal solid waste such as the environmentalist or the decision maker to carryout clean municipal.